Pocketbook-based mental health education: Effects on knowledge and attitudes among Makassar high school students - Azis, Erina Widiyanti; Aswadi, Aswadi; Kurniati, Yessy; Karini, Tri Addya; Rahmat, Rahmat (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2026)
Adolescent mental health literacy remains a major challenge, and practical educational media that can improve both knowledge and attitudes are still needed; this study evaluates a pocketbook as an accessible school-based mental health promotion tool. This study aimed to analyze the effect of pocketbook-based education on high school students’ knowledge and attitudes regarding mental health. A quantitative quasi-experimental study with a pretest-posttest control group design was conducted from March to April 2026 at State Senior High School 12 Makassar and State Senior High School 13 Makassar. A total of 128 students were recruited using convenience sampling and divided equally into intervention and control groups. The intervention group received mental health education using a pocketbook, while the control group received lecture-based education. Both approaches improved students’ knowledge and attitudes; however, post-intervention comparisons using the Mann–Whitney test demonstrated significant differences between the two groups for both outcomes (p<0.001). The pocketbook offered practical advantages by presenting information in an engaging, portable, and reusable format that supports repeated learning. These findings indicate that pocketbook-based mental health education can complement conventional teaching and may be integrated into classroom learning, school health services, and adolescent health promotion programs.